The Spiritual Space of Modern Education: Problems, Theory, Practice. The Interregional Conference in Memory of A. D. Chervyakov - Serova O.E.,; Guseva E.P., (Психолого-педагогические исследования, 2018)
The authors provided information on the first interregional conference of scientific and pedagogical community of the Yaroslavl region dedicated to the memory of the Psychological Institute employee A.D.Chervyakov - scholar, historian of psychology, methodology and organizer of work on the formation of spiritual and moral content of training courses for children and teenagers. In the plenary session speakers invited to discuss a wide range of General methodological issues: the moral lessons of the creative heritage of Russian ascetics, scholars and teachers; the importance of the Orthodox culture in historical educational research context; the practice of the study of old Russian literature as a factor in the spiritual development of students; studying in school and University language of the icon as the basis of spiritually-moral education of a person; moral criteria for the development of the individual student in the modern education; the spiritual foundations of psychological perspectives; ethical and moral standards in the work of the teacher. Discussion at the round table "Youth subculture: tradition and deviation, moral and psychological-pedagogical problems" turned on: a subculture as a tool of socialization and moral formation adolescents; antisocial practices in subcultural spaces; the moral and psychological degradation as a consequence of aggressive subcultural associations; the way to build a dialogue of generations in the modern educational space; the family as an important resource for the confrontation of anti-social effects of youth subcultures; the spiritual and moral traditions of the Yaroslavl region as a means to counter the influence of destructive youth subcultures.